Cadmium in blood and hypertension - Eum, Ki-Do; Lee, Mi-Sun; Paek, Domyung (The Science of the total environment, 2008)
This study is to examine the effect of cadmium exposure on blood pressure in Korean general population. The study population consisted of 958 men and 944 women who participated in the 2005 Korean National Health and Nutrition Examination Survey (KNHANES), in which blood pressure and blood cadmium were measured from each participant. The mean blood cadmium level was 1.67 µg/L (median level 1.55). The prevalence of hypertension was 26.2%. The blood cadmium level was significantly higher among those subjects with hypertension than those without (mean level 1.77 versus 1.64 µg/dL). After adjusting for covariates, the odds ratio of hypertension comparing the highest to the lowest tertile of cadmium in blood was 1.51 (95% confidence interval 1.13 to 2.05), and a dose–response relationship was observed. Systolic, diastolic, and mean arterial blood pressure were all positively associated with blood cadmium level, and this effect of cadmium on blood pressure was markedly stronger when the kidney function was reduced. Cadmium exposures at the current level may have increased the blood pressure of Korean general population.